Innovation in teaching: the use of blended learning approach / Musliha Musman and Salwa Muda - Musman, Musliha; Muda, Salwa (Universiti Teknologi MARA, Negeri Sembilan, 2022)
As technology advances and daily life becomes more digitized, educators actively seek and anticipate engaging in innovative teaching. Innovative teaching methods are proactive methods of teaching that are diametrically opposed to traditional methods in which students learn from educators face to face in the classroom. The purpose of introducing these new teaching methods is to strengthen student understanding so that students can achieve optimal results. There is a significant amount of innovation in education right now, and one of them is blended learning. Blended learning, also known as hybrid learning, is an educational technique that combines the advantages of face-to-face traditional classroom learning methods with online learning methods. It enables both educators and students to gain from the best aspects of both methods. For instance, a student might go to face-to-face classes and then supplement the lesson plan by completing online learning. Online learning is a learning approach that uses innovative ways by utilising internet technology that can be accessible at any time and from any location, allowing learning to occur not only in the classroom and only during class hours, but also outside of class hours when needed (Saragih et al., 2020). Online learning methods include games, movies, tutorials, quizzes, and social networking components that students can access at time and place through their devices such as smartphone or tablet. A study done by Setyaningrum (2018) found that students who learn in blended learning approach have better conceptual understanding than their counterparts. The students claim that they can access learning materials and review some challenging topics at their convenience. AlKhaleel (2019) discovered that 84% of the respondents experience great improvement in their language proficiency abilities as compared to traditional teaching approaches. The study findings, demonstrating that blended learning has a positive impact on students' learning.